2021
DOI: 10.1001/jamaoncol.2021.1074
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Thiotepa-Based Conditioning in Patients With Primary Central Nervous System Lymphoma After Autologous Hematopoietic Cell Transplant

Abstract: IMPORTANCE Primary central nervous system lymphoma (PCNSL) requires induction and consolidation to achieve potential cure. High-dose therapy and autologous hematopoietic cell transplant (AHCT) is an accepted and effective consolidation strategy for PCNSL, but no consensus exists on the optimal conditioning regimens.OBJECTIVE To assess the outcomes in patients with PCNSL undergoing AHCT with the 3 most commonly used conditioning regimens: thiotepa/busulfan/cyclophosphamide (TBC), thiotepa/carmustine (TT-BCNU), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…64 A recent retrospective bone marrow transplant study which included 603 patients demonstrated superiority of thiotepa-based conditioning associated with better threeyear PFS [75% vs 58% with carmustine, etoposide, cytarabine and melphalan (BEAM)]; notably, the upper limit of age for HDT-ASCT was 77 years. 69 Within a large UK retrospective study of patients >65 years, only 22% of patients received consolidation treatment with thiotepa/carmustine HDT-ASCT. Interestingly, this selected subgroup showed two-year PFS and OS rates of 62% and 73%, respectively, 47 which is in line with benchmark trials in younger patients.…”
Section: Treatment Of the 'Very Fit' Elderly With Intensive Hd-mtx-ba...mentioning
confidence: 99%
See 1 more Smart Citation
“…64 A recent retrospective bone marrow transplant study which included 603 patients demonstrated superiority of thiotepa-based conditioning associated with better threeyear PFS [75% vs 58% with carmustine, etoposide, cytarabine and melphalan (BEAM)]; notably, the upper limit of age for HDT-ASCT was 77 years. 69 Within a large UK retrospective study of patients >65 years, only 22% of patients received consolidation treatment with thiotepa/carmustine HDT-ASCT. Interestingly, this selected subgroup showed two-year PFS and OS rates of 62% and 73%, respectively, 47 which is in line with benchmark trials in younger patients.…”
Section: Treatment Of the 'Very Fit' Elderly With Intensive Hd-mtx-ba...mentioning
confidence: 99%
“…Various single‐arm 11,54,64–67 and two randomized trials 10,15,63,68 provide a robust body of evidence for the use of thiotepa‐based HDT–ASCT in younger PCNSL patients <65–70 years with 3–5‐year survival ranging between 69% 15 and 87% 64 . A recent retrospective bone marrow transplant study which included 603 patients demonstrated superiority of thiotepa‐based conditioning associated with better three‐year PFS [75% vs 58% with carmustine, etoposide, cytarabine and melphalan (BEAM)]; notably, the upper limit of age for HDT–ASCT was 77 years 69 …”
Section: Treatment Of Pcnsl In the Elderlymentioning
confidence: 99%
“…In contrast to BEAM or BUCYE, thiotepa has an excellent penetration ability through the central nervous system, with CSF levels greater than 80%, and has been adopted in combination with busulfan, cyclophosphamide, and carmustine in different conditioning regimens (82). Recently, an observational cohort study reported by the Center for International Blood and Marrow Transplant Research (CIBMTR) gave 603 adult PCNSL patients ASCT as either initial or subsequent consolidation therapy (83).…”
Section: Autologous Stem-cell Transplantation (Asct)mentioning
confidence: 99%
“…In this phase 2 study, 56% of patients achieved CR after ASCT with an encouraging 2-year PFS of 46%, after a median follow up of 45 months ( 60 ). Inclusion of thiotepa in the conditioning regimen appears to be key; independently associated with improved outcomes ( 61 , 62 ). Although younger patients are more likely to be considered for HDT-ASCT approaches, a multicenter retrospective study supports this approach in appropriately selected older patients with rrPCNSL (median age: 67 yrs, range: 65−77 yrs) ( 63 ).…”
Section: High Dose Chemotherapy Followed By Autologous Stem Cell Tran...mentioning
confidence: 99%